The Utilization of Digital Technology in Learning Quality Management at State Vocational High School - Nenden Nadya Rizky Mashrul; Abduloh; Ine Rahayu Purnamaningsih; Muhamad Taufik Bintang Kejora (Didaktika: Jurnal Kependidikan, 2025)
This research aims to explore the use of digital technology in the management of learning quality at SMK Negeri 1 Plered, with a focus on the implementation of the PDCA (Plan-Do-Check-Act) cycle in improving the quality of education as initiated by Deming and Sallis. The approach used is qualitative with an exploratory case study method, which allows researchers to explore a deep understanding of the application of digital technology in vocational schools. This research was carried out at SMK Negeri 1 Plered, Purwakarta Regency, West Java, with the main data source involving 6 informants, namely the Principal, Deputy Head of Curriculum, teachers, and 3 students. The data collection technique involved in-depth interviews, observations, and documentation, which were analyzed using interactive models from Miles and Huberman by triangulation to ensure the validity of the findings. The results show that the use of digital platforms such as Google Classroom, Canva, and YouTube plays an important role in increasing learning flexibility, student engagement, and 21st century skill development. However, the main challenges faced are the technology skills gap among teachers and students, as well as limited infrastructure. Suggested follow-up includes improved ongoing training for teachers and the provision of more adequate tools to ensure technology-based learning is optimally accessible to all students. This research provides implications for the development of technology-based learning strategies in other vocational schools to improve the quality of education.